Functional imaging in asthma and COPD: design of the NOVELTY ADPro substudy. Issue 2 (3rd April 2023) - Marshall, Helen; Wild, Jim M.; Smith, Laurie J.; Hardaker, Latife; Fihn-Wikander, Titti; Müllerová, Hana; Hughes, Rod
The NOVEL observational longiTudinal studY (NOVELTY; ClinicalTrials.gov identifier NCT02760329) is a global, prospective, observational study of ∼12 000 patients with a diagnosis of asthma and/or COPD. Here, we describe the design of the Advanced Diagnostic Profiling (ADPro) substudy of NOVELTY being conducted in a subset of ∼180 patients recruited from two primary care sites in York, UK. ADPro is employing a combination of novel functional imaging and physiological and metabolic modalities to explore structural and functional changes in the lungs, and their association with different phenotypes and endotypes. Patients participating in the ADPro substudy will attend two visits at the University of Sheffield, UK, 12±2 months apart, at which they will undergo imaging and physiological lung function testing. The primary end-points are the distributions of whole lung functional and morphological measurements assessed with xenon-129 magnetic resonance imaging, including ventilation, gas transfer and airway microstructural indices. Physiological assessments of pulmonary function include spirometry, bronchodilator reversibility, static lung volumes via body plethysmography, transfer factor of the lung for carbon monoxide, multiple-breath nitrogen washout and airway oscillometry. Fractional exhaled nitric oxide will be measured as a marker of type-2 airways inflammation. Regional and global assessment of lung function using these techniques will enable more precise phenotyping of patients with physician-assigned asthma and/or COPD. These techniques will be assessed for their sensitivity to markers of early disease progression. The NOVELTY ADPro substudy will use functional imaging and physiological and metabolic measures to examine patterns of ventilation, gas transfer, acinar dimensions and small airway dysfunction to phenotype patients with asthma and/or COPD more precisely. https://bit.ly/3GfmN4S